Prevalence and determinants of intention to use modern contraceptives among grand-multiparous women in sub-Saharan Africa - Oluwatobi Abel Alawode; Sylvester Reuben Okeke; Rajeeb Kumar Sah; Obasanjo Afolabi Bolarinwa (BMC, 2022)
Abstract Background Sub-Saharan Africa, characterised by high fertility and low contraceptive use prevalence, remains one of the settings with the poorest maternal and child health indices globally. Studies have established that grand-multiparous women are at increased risk of these adverse maternal health outcomes, and contraceptive use is important to averting these adverse outcomes. Thus, this study examines the prevalence and determinants of intention to use modern contraceptives among grand-multiparous women in 10 sub-Saharan African countries with high fertility rates. Materials and methods The study utilized data from the last installments of the Demographic and Health Survey from the 10 leading countries with the highest total fertility rates in sub-Saharan Africa. These countries include: Angola, Benin, Burundi, Chad, Cote d'Ivoire, the Republic of the Congo, Democratic Republic of Congo, Mali, Niger, and Nigeria. Data analysis of 23,500 grand-multiparous women was done at three univariate levels involving a frequency table and bar chart. We employed bivariate logit and multivariate logit regression at the bivariate and multivariate levels to achieve the study objectives. A significant level was determined at p < 0.05. Results Our study found that less than 40% of grand-multiparous women in these high fertility countries in sub-Saharan Africa, have the intention to use modern contraceptives (39%), but country variations exist with as low as 32.8% in Angola to as high as 71.2% in the Republic of the Congo. The study found that modern contraceptives use intention among grand-multiparous women in these high fertility countries was predicted by a history of contraceptive use and pregnancy termination, exposure to family planning messages on social media, and knowledge of family planning methods. Others were women's fertility planning status, ideal family size, number of marriages (remarriage), couple's fertility desire, current age, and level of education. Conclusion In the high fertility context of sub-Saharan Africa, characterized by low contraceptive use, improving contraceptive use intention among grand-multiparous women is vital for preventing adverse maternal and child health outcomes, including mortality, resulting from a high-risk pregnancy. Hence, interventions should be more innovative in targeting this group of women to increase the contraceptive prevalence rate in line with Family Planning 2030 goals, and ultimately reduce high fertility rates in the region.